The relation given is: D=ABC
It is only possible to express C in terms of the other variables A, B and D by moving them to one side and leaving C on the other.
A*B*C = D
Dividing both sides by A*B leaves C on one side.
C = D/(A*B)
The value of C in terms of the other variables is C = D/(A*B)
To solve D=ABC for C means to come up with an expression for C in terms of all the other variables.
D = ABC
C is being multiplied by A and B. To undo this, we should divide by A and B.
This leaves us with
`(D)/(AB) = C`
Solve D=ABC for C.
(To solve for C you have to get it alone on one side)
To make the C alone, you would have to divide AB
divide both sides of the equation by AB